Pengaruh Permainan Egrang Batok Kelapa Dalam Meningkatkan Keterampilan Anak SD - Rizky Maulana; Olivia Dwi Cahyani; Nurman Ramadhan (Universitas Hamzanwadi, 2026)
The low level of gross motor skills among elementary school students, particularly balance skills, poses a challenge in physical education. This is often caused by a lack of varied, interesting physical activities that are appropriate for children's developmental characteristics. This study aims to examine the effect of the traditional coconut shell stilts game on improving the gross motor skills of upper grade students (grades V-VI). The method used was quantitative with a pre-experimental approach using a one-group pretest-posttest design. The research sample consisted of 23 students from SDN Kliteh who were selected purposively. Data were collected through the Balance Test instrument (Pasarribu, 2020) and analyzed using descriptive statistics and paired sample t-tests. The results showed a significant increase in students' balance scores, from a pretest average of 18.03 to 26.38 on the posttest (p < 0.001). Effect size analysis (Cohen's d = 0.95) indicated a large effect. The conclusion of this study proves that the traditional coconut shell stilts game is effective in improving students' gross motor skills and can be recommended as a simple, contextual, and effective alternative model for physical education learning.